A quest on finding new potential ebola vp40 inhibitors: molecular docking and molecular dynamics simulation studies - Mohamad Yussoff, Mohamad Ariff; Abdul Hamid, Azzmer Azzar; Abd Hamid, Shafida; Abd Halim, Khairul Bariyyah (2018)
Ebola virus is a filamentous virus belonging to Filoviridae family that can cause severe hemorrhagic fever with high fatality rate. Ebola virus matrix protein,VP40 is abundantly expressed during infection and plays several critical roles in oligomerization, budding, viral transcription, and regulation. Interaction of VP40 with RNA is crucial in the early stage of infection to facilitate the transcription of the viral gene. Thus, VP40 is a promising target to inhibit the Ebola virus from spreading. The objective of this study is to identify and optimize ligands that can potentially block RNA binding at the VP40 RNA binding site. A total of 42 compounds from previously studied ligands in the literature were simulated against the RNA binding site using AutoDock Vina. The top ten ligands were then used as templates for similarity search in Zinc databases followed by structured-based virtual screening. The ADMET properties of the compounds were predicted computationally and the binding free energy of the complex was calculated using molecular-mechanics Poisson Boltzmann surface area (MM-PBSA) method to determine the ligands binding affinity. The results showed that Q-88 (ZINC ID: 1342431) is the best ligand with free energy of -97.27 kJ/mol. Our studies revealed that substituting the sulphur (S) atom with oxygen (O) in the backbone structure resulted in better ADME properties with similar binding affinity (-97.097 kJ/mol) against the RNA binding site. Our findings shed light on binding energies and potential modification of previously tested compounds against VP40, which could be useful for the design of new inhibitor of Ebola virus.